Odor-induced phosphorylation of olfactory cilia proteins. - Boekhoff, I (1992)
Stimulation of isolated rat olfactory cilia in the presence of [gamma-32P]ATP leads to a significantly enhanced incorporation of [32P]phosphate. Depending on the type of odorants applied, the induced phosphorylation is completely blocked by specific inhibitors of either protein kinase A or protein kinase C. Time-course experiments indicate that the odor-induced modification of ciliary proteins is transient; the intensity of labeling decayed over time (1-10 sec). Separation of ciliary proteins by SDS/polyacrylamide gel electrophoresis followed by autoradiography demonstrated that upon stimulation with lilial, a single polypeptide (50,000 Da) was phosphorylated; the size of the modified protein is in line with the hypothesis that odorant receptors are phosphorylated subsequent to activation by specific odors.